Pediatricians’ perceptions and practice of the management of constipation in Thailand - Thakoon Wiriyachai (2020)
© 2020 Japan Pediatric Society Background: Previous studies have shown that physicians’ perception and practice can differ from proposed guidelines with regards to constipation. Most studies were performed in developed countries but only a few in developing nations. We therefore aimed to study Thai pediatricians’ perceptions of the management of constipation. Methods: We performed a national survey using an 37-item online questionnaire that included questions about demographics, perceptions, and practice related to constipation in children. We used a five-point scale to determine perception in each aspect (5 = strongly agreed; 1 = strongly disagreed). Results: We received 275 responses (response rate of 11.0%). Most were female (69.1%), subspecialists (55.6%) and worked in a government-based setting (69.5%). We noted that only 51.8% considered disimpaction if physical examination is suggestive of fecal impaction. Most pediatricians used lactulose for both disimpaction and maintenance phases (83.4 and 91.9%, respectively); however, pediatricians perceived that the caregivers of constipated children were concerned about tolerance or dependence of most commonly used laxatives, ranged from 45.8 to 63.8%. We also found that recently graduated pediatricians were more likely than older individuals to provide advice on fluid intake, toilet training, and laxative use, and to consider polyethylene glycol for disimpaction (P = 0.003, 0.02, 0.004, and 0.02, respectively). Conclusions: The proportion of pediatricians who consider disimpaction remained suboptimal. Providing appropriate knowledge on pharmacological management, especially disimpaction and issues regarding laxatives, may be helpful for pediatricians and caregivers. Education may also need to be tailored to various pediatricians’ experience and work settings.